2016
DOI: 10.1186/s12893-016-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Major postoperative complications are associated with impaired long-term survival after gastro-esophageal and pancreatic cancer surgery: a complete national cohort study

Abstract: BackgroundSome studies have reported an association between complications and impaired long-term survival after cancer surgery. We aimed to investigate how major complications are associated with overall survival after gastro-esophageal and pancreatic cancer surgery in a complete national cohort.MethodsAll esophageal-, gastric- and pancreatic resections performed for cancer in Norway between January 1, 2008, and December 1, 2013 were identified in the Norwegian Patient Registry together with data concerning ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…Similarly, surgical stress can lead to the onset of prothrombotic and immunosuppressive changes during the postoperative period 2,3 . Many correlative studies have confirmed an association between postoeprative complications, immune suppression and worsened cancer survival [4][5][6][7] . Our group and others have proposed surgery-induced cellular immune suppression as a primary factor in the progression of cancer, including local recurrence and metastases [8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, surgical stress can lead to the onset of prothrombotic and immunosuppressive changes during the postoperative period 2,3 . Many correlative studies have confirmed an association between postoeprative complications, immune suppression and worsened cancer survival [4][5][6][7] . Our group and others have proposed surgery-induced cellular immune suppression as a primary factor in the progression of cancer, including local recurrence and metastases [8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 96%
“…Postoperative complications impact patients' oncologic outcomes and have been associated with impaired survival in esophageal and gastric cancer . This might be related to postoperative weight loss and worsened nutritional status, which could, along with previous comorbidities, lead to performance status decline and worse overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have shown that such postoperative complications frequently reduce the overall survival (OS) as well as cancer‐specific survival after major surgery for cancer 9. In particular, severe postoperative complications are associated with impaired long‐term survival after gastroesophageal and pancreatic cancer surgery 10. One possible explanation for this phenomenon is that the changes in patient immunological responses trigger the progression of residual disease into a clinically manifest recurrence 11.…”
Section: Introductionmentioning
confidence: 99%